English lexical items in Chinese business advertisements in Malaysia - Kuang, Ching Hei; Lau, Su Kia; Choo, Wee Ling; Doshi, Asha (Journal of Modern Languages, 2017)
According to Mclaughlin, 1984 (in Hoffman 1991), code mixing occurs within the sentential level and usually involves the use of lexical items. It has been found code mixing does not only exist in conversations among the language users in Malaysia, but it also exists in business advertisements in Malaysian Chinese dailies. In particular, the use of Chinese (Mandarin) and English concurrently in these advertisements seem rampant. The study hopes to identify the roles of English lexical items used in these advertisements as well as to provide more information on how the use of English lexical items in Chinese business advertisement can lure customers. A maximum of one hundred sentences in Malaysian Chinese advenisements were collected from China Press, Oriental Daily, Nanyang Slang Pau and Guang Ming Daily from July 2005 to December 2005. The researchers also interviewed five individuals from the Chinese advertising industry to identify the roles of English lexical items that have been code mixed into the advertisements. It has been identified that nouns, verbs and adjectives in English were often more predominantly used in the themes of sentences in Chinese business advertisements. Some proper nouns in English were not translated into Chinese to preserve the concept and to ease understanding. Besides that, English abbreviations such as "CO", "VCD", "DVD", "SMS" and "IT' were inserted into the Chinese advertisements, making the sentences simpler and easier to understand. In addition, English adjectives such as "in", "kick" and "hot" were inserted into Chinese advertisements to create a sense of stylishness and to exert some sense of modernity, to attract the attention of the young generation. Interjections such as "wow" and "yeah" were also inserted into Chinese advertisements. This occurrence causes the sentences in advertisements to have more spoken features and hence, more easily acceptable among the readers in general. It was also discovered that "No. 1" was inserted into the advertisements to increase the status of the products and services advertised. At times , the extensive usc af"No. 1" in Chinese advertisements can also be seen as one of the techniques of advertising.